Research on a Master Manipulator Using an Isometric Interface for Translation in Robotic Surgery. (17th September 2015) - Kim, In; Kanno, Takahiro; Tadano, Kotaro; Kawashima, Kenji
In surgery with a master-slave type of surgical robot, an anisometric interface is often used. The working range of the master side is limited, so repositioning is required. Any repositioning from the master side will disturb the robot's operation. In this study, an operation interface is proposed that uses only the operator's force input for translational directions. A force sensor is used to detect this input. A gimbal mechanism is mounted on the sensor which allows for rotation. The rotation accounts for the operator's input rotation, and as a result the mechanism can now match the input. This allows the operator to concentrate on the slave side and control the robot without repositioning. The authors developed the proposed interface to control the pneumatically driven slave robot. The block transfer experiments confirmed that the proposed interface has nearly the same performance as conventional interfaces.